200. Frequency and Characteristics of Patients Switched from Intravenous to Oral Antibiotic Therapy on Discharge to Nursing Homes - Colangeli, Hailey N (Open Forum Infect Dis, 2020)
BACKGROUND: Determining eligibility for intravenous (IV) to oral (PO) antibiotic conversion is challenging in patients transitioning to nursing homes (NHs) due to atypical infection presentation, increased diagnostic uncertainty, and multimorbidity. Understanding current practice and patient characteristics influencing prescriber behavior is necessary to provide effective antibiotic stewardship in this vulnerable population. We compared the frequency and characteristics of patients discharged with IV antibiotics to those switched from IV to PO therapy. METHODS: This was a retrospective cohort study of Oregon Health & Science University Hospital patients treated with IV antibiotics and discharged to a NH from 1/1/2016-12/31/2018. We focused on IV to PO antibiotic switch within 48 hours of discharge. Using a repository of electronic health record data, we collected patient demographic, diagnosis, length of stay, and treatment duration data. RESULTS: Among 2,410 patients discharged to a NH on antibiotics, 1,483 (61.5%) received an IV antibiotic within 48 hours of discharge. IV to PO switch occurred in 46.7% of patients prior to discharge, and these patients had fewer baseline comorbidities (Table 1). Of those continuing IV antibiotics, 96.1% were prescribed a different PO medication at discharge indicating potential to take PO medications. Cephalosporins (45%) and penicillins (22%) were the most commonly prescribed IV antibiotics, with IV to PO conversion rates of 26% and 46%, respectively. The median (interquartile range) outpatient duration of therapy was 21 (12–33) days for IV antibiotics and 7 (4–10) days for PO antibiotics. Osteomyelitis diagnosis was more frequent among IV therapy patients; pneumonia and urinary tract infections were more frequent in IV to PO switch patients. IV to PO switch patients were less likely to experience a hospital stay > 7 days or receive an infectious disease consult (p < 0.001). Table 1. Comparison of Patient and Treatment Characteristics among IV and Oral Antibiotic Prescriptions on Discharge [Image: see text] CONCLUSION: The proportion of patients discharged to a NH on IV antibiotics remains high, even among patients able to tolerate PO medication. Continuing IV therapy was associated with longer treatment durations, hospital stays, and broad spectrum regimens, while patients with IV to PO switch had a higher comorbidity burden at baseline. DISCLOSURES: All Authors: No reported disclosures